Implementation of Character Education and National Culture through Civic Education Subjects in Elementary Schools - Zubaidah Zubaidah (Indonesian Journal of Character Education Studies, 2024)
The issue of culture and national character is now in the spotlight. The spotlight is on various aspects of life, contained in various writings in the print media, interviews, dialogs, and talk shows on electronic media. The purpose of this research is to find out the implementation of national character and culture education in primary schools through civic education subjects. The research approach uses descriptive qualitative with field research method. The data sources in this study include two types, namely primary and secondary data. The data collection process used three methods including observation, interviews, and documentation. Checking the validity of data researchers use triangulation techniques. Data analysis through the process of (1) data reduction; (2) data presentation; (3) conclusion. The results of the study concluded that the process of implementing the values of character education and national culture carried out by teachers at SDN 115 Seluma was carried out through learning activities, developing school culture and learning activity centers, and extracurricular activities. This research contributes as an enrichment material and knowledge information both theoretically and practical studies on the implementation of character education and national culture in schools through civic education subjects.